THE MAIN ASPECTS OF DIAGNOSIS AND PREVENTION OF OPISTHORCHIASIS - Помыткина, Татьяна Евгеньевна; Пивовар, Ольга Ивановна (Medicine in Kuzbass, 2025)
The aim of the research – to identify the features of clinical manifestations and laboratory diagnostics of chronic opisthorchiasis in adults and children.Materials and methods. The medical histories of 170 patients (74 children and 96 adults) with chronic opisthorchiasis aged 4 to 83 years who were hospitalized for anthelmintic therapy in an infectious diseases hospital were retrospectively studied and analyzed. The evaluation of complaints, epidemiological history, clinical and biochemical data and specific research methods was carried out: coprooscopy, bile microscopy, enzyme immunoassay of blood and polymerase chain reaction of feces.Results. Analysis of the study results showed that the leading clinical manifestations of opisthorchiasis in children were cholangiocholecystitis and gastroduodenitis. With an invasion duration of more than 3-5 years, adult patients showed a polymorphism of clinical symptoms with the development of cholangiocholecystitis, pancreatitis, hepatitis and gastroduodenitis, which were recorded statistically significantly more often than in children.Conclusion. Opisthorchiasis remains a significant clinical problem in modern medicine. The implementation of therapeutic, preventive, sanitary, hygienic and educational measures in opisthorchiasis-endemic regions has led to a decrease in morbidity in the Russian Federation over the past decade. Epidemiological history and clinical and instrumental data are especially important for early detection of opisthorchiasis, and a combination of immunological and parasitological research methods will improve the quality of timely diagnosis.
Keywords: opisthorchiasis invasion; cholangitis; cholecystitis; gastroduodenal dyspepsia; cholangiohepatitis; pancreatitis; helminthoscopy